Assessing the Mechanisms Thought to Govern Ice and Snow Friction and Their Interplay With Substrate Brittle Behavior - Lever, James H.; Asenath-Smith, Emily; Taylor, Susan; Lines, Austin P. (Frontiers in Mechanical Engineering, 2021)
Sliding friction on ice and snow is characteristically low at temperatures common on Earth’s surface. This slipperiness underlies efficient sleds, winter sports, and the need for specialized tires. Friction can also play a micro-mechanical role affecting ice compressive and crushing strengths. Researchers have proposed several mechanisms thought to govern ice and snow friction, but directly validating the underlying mechanics has been difficult. This may be changing, as instruments capable of micro-scale measurements and imaging are now being brought to bear on friction studies. Nevertheless, given the broad regimes of practical interest (interaction length, temperature, speed, pressure, slider properties, etc.), it may be unrealistic to expect that a single mechanism accounts for why ice and snow are slippery. Because bulk ice, and the ice grains that constitute snow, are solids near their melting point at terrestrial temperatures, most research has focused on whether a lubricating water film forms at the interface with a slider. However, ice is extremely brittle, and dry-contact abrasion and wear at the front of sliders could prevent or delay a transition to lubricated contact. Also, water is a poor lubricant, and lubricating films thick enough to separate surface asperities may not form for many systems of interest. This article aims to assess our knowledge of the mechanics underlying ice and snow friction. We begin with a brief summary of the mechanical behavior of ice and snow substrates, behavior which perhaps has not received sufficient attention in friction studies. We then assess the strengths and weaknesses of five ice- and snow-friction hypotheses: pressure-melting, self-lubrication, quasi-liquid layers, abrasion, and ice-rich slurries. We discuss their assumptions and review evidence to determine whether they are consistent with the postulated mechanics. Lastly, we identify key issues that warrant additional research to resolve the specific mechanics, and the transitions between, them that control snow and ice friction across regimes of practical interest.